A SPEECH ACT ANALYSIS OF CONDOLENCE UTTERANCES FOR THE DEATH OF QUEEN ELIZABETH II IN FACEBOOK USERS - Mentari, Putri; Susiati, Susiati (Lire Journal (Journal of Linguistics and Literature), 2024)
The study focused on investigating speech acts and condolence strategies expressed by Facebook users in BBC posts. This research intends to classify and find out the speech acts and condolence strategies used by Facebook users to the death of Queen Elizabeth II. This research uses a qualitative approach, utilizing data sourced from condolence utterances used by Facebook users. The data were taken from comments posted by users on Facebook News. The data collection through documentation techniques. The data were analyzed by using Searle (1976) and using Zunin & Zunin (1991). The result explains that there are six types of condolence strategies found. The most common condolence strategy was taking note of the quality of the deceased with eighteen data. Second, ending with a thoughtful word with seventeen utterances. Expression of sympathy and taking note of a special quality of the bereaved with thirteen data. Then, acknowledge the loss which found nine data. The last, retelling a special memory of the deceased only eight data. Then, the dominant type of illocutionary act used by Facebook users to the death of Elizabeth Queen II was expressive with a total of fourteen data. Meanwhile, directives were revealed to be the least used by Facebook users, with only two data.